2021
DOI: 10.33549/physiolres.934722
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of High-Intensity Interval Training (HIIT) on Postexercise Intramuscular Lipid Metabolism in Rats

Abstract: Recovery from exercise refers to the period between the end of a bout of exercise and the subsequent return to a resting or recovered state. It is a dynamic period in which many physiological changes occur. A large amount of research has evaluated the effect of training on intramuscular lipid metabolism. However, data are limited regarding intramuscular lipid metabolism during the recovery period. In this study, lipid metabolism-related proteins were examined after a single bout of exercise in a time-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…High-intensity interval training (HIIT) can result in metabolic adaptations of skeletal muscle, which include IMTG accumulation and mitochondrial content increase. Data collected in our lab have validated this point: Chen and Zhou et al found that a 5-week HIIT regimen increased the content of IMTG [ 4 , 5 ]. Our published results also suggest that a 6-week HIIT program can induce IMTG accumulation and elevate the amount of mitochondria in skeletal muscle [ 34 ].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…High-intensity interval training (HIIT) can result in metabolic adaptations of skeletal muscle, which include IMTG accumulation and mitochondrial content increase. Data collected in our lab have validated this point: Chen and Zhou et al found that a 5-week HIIT regimen increased the content of IMTG [ 4 , 5 ]. Our published results also suggest that a 6-week HIIT program can induce IMTG accumulation and elevate the amount of mitochondria in skeletal muscle [ 34 ].…”
Section: Introductionmentioning
confidence: 75%
“…The study discovered that the cAMP–PKA pathway regulated the inhibition of lipolysis, leading to lactate-induced accumulation of IMTG. Lactate injection might also increase mitochondria content, while the contributions of the cAMP–PKA pathway might be limited [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…2D), further confirming their fatigue-prone phenotype. To further support the importance of BDNF in muscle recovery after exercise, mice were subjected to two consecutive exhaustive tests with a 6-hour recovery in between, which is sufficient to replenish the IMTG in normal mice ( 36 ). Although Fl/Fl mice displayed no reduction in running endurance after the first test, the running capability of MBKO mice was significantly reduced in the second test (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because PPARδ activity is also essential to maintaining FA uptake ( 52 ), it seems logical to hypothesize that PPARδ plays a role in post-exercise IMTG recovery. Intramyocellular FAs have been suggested to induce Ppard expression, but this hypothesis is contradicted by FA incubation failing to alter Ppard expression in cultured myotubes ( 12 , 36 ). Hence, the upstream factor that promotes Ppard expression after exercise remains unknown ( 12 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Test item selection. different distances, which require the athletes to complete the training at the fastest possible speed, and the content of the movements developed in the training should be similar to the structure of the boxing game[7][8][9].…”
mentioning
confidence: 99%